Doing it for themselves: the practices of amateur musicians and DIY music networks in a digital age - Hoare, Michaela; Benford, Steve; Greenhalgh, Chris; Chamberlain, Alan (2014)
A fast expanding network of DIY music communities in the UK see digital technologies transforming ways in which part-time amateur musicians are able to collabo- rate creatively and form alliances, producing unique per- formance techniques, experimenting with genre conven- tions and reaching out to an international audience. With a DIY approach, creative autonomy and control is re- tained and celebrated in shared non-commercial spaces run by the artists themselves. A rich ethnographic study seeks to explore these shared ideologies and practices.